Rethinking Efforts to Ground the Helicopter Parent: Parent Experiences Providing Support to Young Adults With Disabilities. (December 2019) - Francis, Grace L.; Reed, Alexandra S.
Transitioning out of school is often challenging, especially for young adults with disabilities. Fortunately, parent involvement can enhance the transition process and student outcomes following graduation. However, there is limited information regarding how and why parents provide support to their young adults in high school and college, thus reducing the ability for professionals to maximize parental investment in the well-being of their young adults. The purpose of this study was to learn about parent experiences providing support to their children with disabilities as they age into adulthood. A total of 26 parents of postsecondary education program (PSE) graduates participated in interviews. Participants described how they provided support to their young adults, discussed reasons why they provided support, and offered recommendations for other parents to effectively support their children with disabilities as they age into adulthood.